1971
DOI: 10.3758/bf03332484
|View full text |Cite
|
Sign up to set email alerts
|

Stimulus relevancy and transfer of perceptual learning

Abstract: Albino rats reared in a visually sparse environment were preexposed to stimuli wh ich varied in their degree of relevancy to the to·be-discriminated stimuli, an equilateral triangle and a circle. It was found that for early experience with stimuli to facilitate perceptual learning, the preexposed stimuli must be of the same general dass as the to-be-discrirninated stimuli. These findings suggested that the positive transfer effect which follows preexposure to stimuli results from identifying specific aspects o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
8
0

Year Published

1972
1972
1996
1996

Publication Types

Select...
8
2

Relationship

2
8

Authors

Journals

citations
Cited by 16 publications
(8 citation statements)
references
References 5 publications
0
8
0
Order By: Relevance
“…It is especially under these circumstances that the account of perceptual learning provided by McLaren et al (1989) would expect familiarization to facilitate, rather than retard, subsequent discrimination learning. The difference is reminiscent of that observed in some yet earlier experiments on perceptual learning in rats (e.g., Bennett, Anton, & Levitt, 1971;Forgus, 1958aForgus, , 1958bGibson, Walk, Pick, & Tighe, 1958), in which preexposure was particularly likely to facilitate subsequent discrimination if the test stimuli involved slight distortions of those to which subjects had been preexposed. Hall and Channell (1980) might equally have appealed to the concept of acquired equivalence to explain their results.…”
Section: Discussionmentioning
confidence: 52%
“…It is especially under these circumstances that the account of perceptual learning provided by McLaren et al (1989) would expect familiarization to facilitate, rather than retard, subsequent discrimination learning. The difference is reminiscent of that observed in some yet earlier experiments on perceptual learning in rats (e.g., Bennett, Anton, & Levitt, 1971;Forgus, 1958aForgus, , 1958bGibson, Walk, Pick, & Tighe, 1958), in which preexposure was particularly likely to facilitate subsequent discrimination if the test stimuli involved slight distortions of those to which subjects had been preexposed. Hall and Channell (1980) might equally have appealed to the concept of acquired equivalence to explain their results.…”
Section: Discussionmentioning
confidence: 52%
“…Numerous studies have been conducted to investigate the effect of early visual form exposure on subsequent discrimination learning (Baird & Becknell, 1962;Bennett, Anton, & Levitt, 1971;Cool, 1967;Fergus, 1956Fergus, , 1958aFergus, , 1958bGibson & Walk, 1956;Gibson, Walk, & Tighe, 1959;Kawachi, 1965;Kerpelman, 1965;Libaw, 1961;McCall & Lester, 1969;. However, no attempt has been made to investigate the effect of particular levels of preexposure pattern difficulty on subsequent learning.…”
Section: Relationship Between Level Of Visual Pattern Difficulty Duri...mentioning
confidence: 99%
“…Previous studies with rats have shown that exposure to forms during rearing (e.g., circles and triangles) can have a significant impact on learning a form discrimination task involving the same or similar forms (e.g., Bennet & Ellis, 1968;Forgus, 1958a, b;Gibson & Walk, 1956;Kerpelman, 1965). However, no transfer has been found when the rearing and test forms were very different (Bennett, Anton, & Levitt, 1971;Gibson, Walk, Pick, & Tighe, 1958). A common interpretation for this lack of transfer was that the subjects in studies that had found transfer had learned to pay attention to visual cues which later became the basis for the learned discrimination (Bennett et aI., 1971;Gibson, 1969, pp.…”
mentioning
confidence: 87%